2022
DOI: 10.1111/josh.13199
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Suicidal Behaviors Among US High School Students*

Abstract: BACKGROUND: Food insecurity (FI) rates in the United States are particularly high among households with children. This research set aims to analyze if high school students experiencing FI had higher risk for mental health and suicidal behaviors. METHODS:Using combined data from 11 states that conducted the 2017 Youth Risk Behavior Survey, a total of 26,962 and 24,051 high school students were used to estimate race/ethnicity and sex-stratified prevalence ratios (PRs) from Poisson regression models. A single-que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
3
6
1
Order By: Relevance
“…With regard to food insecurity among adolescents, a cross-sectional study of 179,771 adolescents from 9 high-income, 31 middle-income, and 4 low-income countries found an association between food insecurity (hunger) and suicide attempts [ 35 ]. A study conducted among US high school students [ 36 ] also demonstrated an association between food insecurity and both suicidal ideation and suicide attempts, which is consistent with our findings. Food insecurity has recently become a major issue in Lebanon, with 42% of the country’s population facing it by 2023[ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…With regard to food insecurity among adolescents, a cross-sectional study of 179,771 adolescents from 9 high-income, 31 middle-income, and 4 low-income countries found an association between food insecurity (hunger) and suicide attempts [ 35 ]. A study conducted among US high school students [ 36 ] also demonstrated an association between food insecurity and both suicidal ideation and suicide attempts, which is consistent with our findings. Food insecurity has recently become a major issue in Lebanon, with 42% of the country’s population facing it by 2023[ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous research showing that children and adolescents experiencing food insecurity are more likely to have symptoms of depression and anxiety, a worsening of ADHD symptoms and other behavioural issues. 7 10 , 17 , 24 26 Food insecurity has also been associated with suicidal ideation and attempts among adolescents, 8 , 9 , 27 but we found no indication of a higher prevalence of acute care visits for self-harm, although these were uncommon in our sample. The coexistence of household food insecurity and service use for mental and substance use disorders is problematic, given that both of these conditions have each been found to have negative consequences for social, educational and developmental outcomes among children and adolescents.…”
Section: Discussioncontrasting
confidence: 72%
“…31 The severity of symptoms was classified based on predetermined thresholds for mild, moderate-to-severe, and severe symptoms. For depression, the cutoff points were: normal (0-9), mild (10-13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (+28). Similarly, for anxiety, the thresholds were: normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe (+20).…”
Section: Depression Anxiety and Stressmentioning
confidence: 99%